Kajian kecenderungan antenatal care di Kota Tomohon periode 2015-2017 - Mampuk, Angela S. K.; Siagian, Iyone E. T.; Palandeng, Henry M. F. (UNIVERSITAS SAM RATULANGI, 2018)
Background: Antenatal Care (ANC) is a service provided to pregnant women to facilitate pregnancy that is good for the mother and fetus and as a step to conceptualize the early hours of the events that occur in the mother and fetus, and as preparation for labor. The Sustainable Development Goals (SDGs) target, in 2030, all countries must reduce the number of maternal mortality in 2010.Aim: This research intended to describe the liability of pregnant women to go to antenatal care.Methods: The type of research used is a cross-sectional study design with descriptive and using secondary data taken from the Tomohon City Health Profile book for 2015-2017. Results: The results showed that from 2015-2017 there was an increase in K-1 visits by 3.7% and a decrease in K-4 visits by 1.6%. There was 1 incident of maternal death in 2016. Conclusion: The conclusion of the results of this study is that there has been an increase in the achievement of K1 and K4, as well as the achievement of integrated antenatal care.